Analysis Of Rock Fragmentation By Using Powersieve Software - Ragunathan, Logatharan (Universiti Sains Malaysia, 2017)
The ability of blasting operations can be esteemed relying upon the reason on the purpose in various ways. It depends whether blasting is done in mineralized or the sterile zone in mining operations. In mineralized zone, the primary stage of the general comminution process is blasting and its purpose is to produce a specific fragment size appropriate for succeeding ore handling and mineral processing (Hudson, 1993) .Usually, these means are based on evaluation fragment size consequential from blast (J.Aler, J.Mouza Du, M.Arnould, 1996). There are various factors that affect the fragmentation of granite rocks. These can be divided into controlled and uncontrolled factors. The controllable factors such as burden, spacing, bench height, powder factor, sub-drilling, stemming, sequence of blast initiation and diameter of holes. The uncontrollable concern more towards geological structure of rocks. (Orica, Safe and Efficient Blasting in Quarries, 2008). In this research the main concern is more towards controlled factors. Point load test carry out on rock samples to make sure that the strength and geological structure is constant in the area selected to be blasted for purpose of this research. The most common factor used to state a fragmentation of blasting is ‘powder factor’ (Rizza, 2017) .However, in this research, blasting performance is analysed with other factors such as relative bulk strength and type of detonation. The practical part of the research was carried out at Batu Tiga Quarry (BTQ) Masai, Johor. This research is divided into three stages, (1) site observation, (2) data analysis and (3) sample testing. Site observation recognizes what is the value of powder factor perfect to be utilized the condition and geographical structure on research area was observed. In data analysis, the images of muck piles were captured, the images are then transferred into the PowerSieve software. PowerSieve software used to perform analyses and evaluates the pictures taken and get the fragmentation distribution, cumulative passing percentage and cover area percentage. The sample testing involves point load test on rock samples collected from blast area to determine the strength of the rocks. The analysis shows that electronic detonation produces a better fragmentation compared to non-electric detonation. In the meantime, explosive with high relative bulk strength have better fragmentation. The usual factor which is used for fragmentation analysis is Powder Factor. In this research, two blast were included as a standardized matter to show the effects of Powder Factor on blast fragmentation. The point load test is taken to show the effect of uncontrollable factor on the blast fragmentation that is the strength of rocks.